2021
DOI: 10.3390/molecules26102838
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Statins on Neurotransmission and Their Neuroprotective Role in Neurological and Psychiatric Disorders

Abstract: Statins are among the most widely used drug classes in the world. Apart from their basic mechanism of action, which is lowering cholesterol levels, many pleiotropic effects have been described so far, such as anti-inflammatory and antiatherosclerotic effects. A growing number of scientific reports have proven that these drugs have a beneficial effect on the functioning of the nervous system. The first reports proving that lipid-lowering therapy can influence the development of neurological and psychiatric dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 152 publications
0
11
0
Order By: Relevance
“…Statins could significantly reduce depression and hospitalization in patients prone to psychiatric disorders 8 . Moreover, based on several studies, use of statin is correlated with less severe symptoms in patients with neurodegenerative diseases such as AD and Parkinson's disease (PD) 9 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Statins could significantly reduce depression and hospitalization in patients prone to psychiatric disorders 8 . Moreover, based on several studies, use of statin is correlated with less severe symptoms in patients with neurodegenerative diseases such as AD and Parkinson's disease (PD) 9 …”
Section: Introductionmentioning
confidence: 99%
“…8 Moreover, based on several studies, use of statin is correlated with less severe symptoms in patients with neurodegenerative diseases such as AD and Parkinson's disease (PD). 9 There have been reports on the probable effect of statins on future AD development. Recently, a meta-analysis conducted by Zhang et al concluded that statins, by inhibiting the formation of intracerebral amyloid, have a protective role against dementia and AD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As possible etiological factors of VaD are atherosclerotic vascular lesions, one of the important areas of treatment is lipid metabolism analysis and drug treatment for dyslipidemia [ 13 , 14 ]. Statins are regarded as the most common lipid-lowering drugs and are 3-hydroxy-3-methylglutaryl-coenzyme A reductase [HMG-CoA reductase (HMGCR)] inhibitors that are the rate-limiting enzymes in the mevalonate pathway [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pleiotropic effects are therapeutic effects that are not related to the original main effect. For statins, mainly anti-inflammatory, immunomodulatory, and vascular endothelium-protective effects [25,29], as well as neuroprotective effects [30][31][32] have been demonstrated, which can also meaningfully intervene in the disease process in POAG. Experimentally, neuroprotective effects have been demonstrated in an OHT animal model [33].…”
mentioning
confidence: 99%